2020
DOI: 10.3389/fpsyg.2020.00036
|View full text |Cite
|
Sign up to set email alerts
|

Role Stress and Turnover Intention of Front-Line Hotel Employees: The Roles of Burnout and Service Climate

Abstract: High turnover rate represents one of the most significant challenges the hotel industry faces. High turnover rates mean labor shortages, resulting in high costs of recruiting, staffing and training. Turnover also has a negative impact on service quality. Scholars continue to search for the root causes of turnover and propose solutions. To further understand employees' turnover intention, this study reveals the role of stress on hotel front-line employees' turnover intention through the mediation of burnout. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
84
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 83 publications
(132 reference statements)
11
84
2
5
Order By: Relevance
“…Faulkner and Patiar (1997) found "too much work" to be a common stressor for hotel operational staff, and Hwang et al (2014) identified problems related to "too much work" and "working long hours" as one of the critical aspects of work stress among hotel employees. Thus, unsurprisingly, employees who face work overload may be more likely to experience emotional exhaustion (Wen et al, 2020), which is also confirmed in empirical findings of previous studies. For example, Essawy (2016) in his study among employees of Quick Service Restaurants (QSRs) confirmed a positive association between overloaded employees and their emotional exhaustion.…”
Section: Antecedents Of Emotional Exhaustionsupporting
confidence: 83%
See 4 more Smart Citations
“…Faulkner and Patiar (1997) found "too much work" to be a common stressor for hotel operational staff, and Hwang et al (2014) identified problems related to "too much work" and "working long hours" as one of the critical aspects of work stress among hotel employees. Thus, unsurprisingly, employees who face work overload may be more likely to experience emotional exhaustion (Wen et al, 2020), which is also confirmed in empirical findings of previous studies. For example, Essawy (2016) in his study among employees of Quick Service Restaurants (QSRs) confirmed a positive association between overloaded employees and their emotional exhaustion.…”
Section: Antecedents Of Emotional Exhaustionsupporting
confidence: 83%
“…Having in mind the findings of this study, hotel management should also regularly check their frontline employees' level of job stress to protect them from experiencing emotional exhaustion and its negative consequences. Thus, if the job stress reaches a certain threshold, managers should take adequate actions, such as, for example, allowing employees to take time off to recharge (H-M. Choi et al, 2019;B. Wen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations